Civil Society Report to the Commission on Social Determinants of Health - Representatives of Civil Society (Social Medicine Publication Group, 2007)
A hundred and fifty years after his death we continue to be reminded of Virchow's comment: "Do we not always find the diseases of the populace traceable to defects in society"? We continue to seek "defects in society" that need to be remedied if health is to be given its rightful place. Today, more so than ever before, we are reminded that, ultimately, politics played out at the global scale, determines whether people live or die. Civil Society welcomes the opportunity provided by the Commission on Social Determinants of Health (CSDH) to explore these issues in detail. Civil Society has been consistent in arguing for an approach to health that echoes Virchow's famous words.